Preparation of nano-magnesium oxide from Indonesia local seawater bittern using the electrochemical method. Issue 8 (2nd August 2020) - Amrulloh, Hanif; Simanjuntak, Wasinton; Situmeang, Rudy Tahan Mangapul; Sagala, Sophia Lasma; Bramawanto, Rikha; Fatiqin, Awalul; Nahrowi, Ridho; Zuniati, Mai
Abstract: In this study, nano-size MgO was synthesized from seawater and bittern obtained from local salt industry in Pamekasan, Madura, Indonesia, using electrochemical method. The main purpose was to study the effects of seawater pre-concentration and bittern dilution on the structure and morphology of the MgO nanoparticles produced. Electrochemical process was performed in a two-compartment electrochemical cell with a fixed potential of 18 V, for 4 h at ambient temperature, and without adjusting the pH. Solid Mg(OH)2 produced was converted into MgO by calcination treatment at 500 °C for 4 h, and then characterized using XRD and SEM technique. The characterization results revealed that spherical or cubic crystalline MgO were successfully produced, with the particle sizes in the range of 60–100 nm.